Oxygen is a better predictor of macroinvertebrate richness than temperature-a systematic review - Croijmans, L; De Jong, J F; Prins, H H T (Environmental research letters, 2021)
Despite ongoing loss of diversity in freshwater ecosystems, and despite mitigation measures to halt this loss, it is still not clear what ecological drivers underlies lotic biodiversity. A complicating factor is that two of the main drivers, oxygen and temperature, are correlated, and hence studies towards drivers of lotic diversity are confounded. Here, we undertook a systematic review, consisting of both qualitative and quantitative analyses, to disentangle these two drivers. We accessed two literature repositories and assessed papers for eligibility using a set of predetermined criteria. For the qualitative part of this systematic review, we used results on patterns of taxonomic richness and multivariate ordination analyses to expose effects of temperature and dissolved oxygen concentration on biodiversity. For the meta-analysis, we could only use raw data of a few papers in generalized linear models. The qualitative analysis did not show strong consistent effects of either dissolved oxygen concentration or temperature on diversity. However, the meta-analysis showed that taxonomic richness is positively related with dissolved oxygen concentration. Inversely a negative correlation with temperature was found, but adding temperature to a model which already included dissolved oxygen content did not significantly improve the model. These results show the strength of a systematic review and meta-analysis over a conventional review without a meta-analysis; we found no pattern with the qualitative analysis, but a strong pattern with the quantitative analysis.